Visual impairment and falls among older adults and elderly: evidence from longitudinal study of ageing in India - Rajeev Ranjan Singh; Priya Maurya (BMC, 2022)
Abstract Background The present study determines the prevalence and correlates of falls, multiple falls, and injuries, focusing on visual impairment among the older adult and elderly population in India. Additionally, owing to the higher prevalence of falls and visual impairment among women, a sex-stratified analysis has also been done in the present study. Methods The study utilized the data from the first wave of the Longitudinal Ageing Study in India (LASI wave-1), conducted during 2017-2018. Bivariate with chi-square and multivariate analyses were performed to fulfill the objective. Results Around 34% of population had low vision (male:30% and female: 38%), while blindness prevalence was 1.63% (males: 1.88% and females: 1.41%). The fall was higher among females and increased across the gender with increasing visual impairment and blindness levels. The unadjusted odds of falls were 16% higher among individuals with low vision and 40% higher among individuals with blindness than with normal vision, and comparatively higher odds among females than males. Conclusion In summary, falls and visual impairment is public health challenge and needs to be addressed. Visual impairment is preventable in most cases, so it may be a modifiable target for reducing the risk of falls.